Preparation method and application of lignin-containing cellulose nanofiber / aramid nanofiber composite membrane

Through the combination of the modified aramid nanofiber extracted and cellulose nanofibers, the composite membrane has been solved, and the efficiency and performance of dye wastewater treatment has been significantly improved, and high strength and efficiency have been achieved. Dye removal.

CN119119534APending Publication Date: 2024-12-13SHANDONG UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411366957.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing lignin-containing cellulose nanofiber composite membranes have poor toughness and brittleness in dye wastewater treatment, and the chemical inert surface of aramid nanofibers leads to poor interfacial compatibility, which limits its performance improvement.

Method used

The ultra-strong alkali system is used to extract lignin-modified aramid nanofibers, and combine with cellulose nanofibers through the viscosity and homology of lignin to form a high-strength cellulose nanofiber/aramid nanofiber composite membrane, using π- π interaction and hydrogen bonding enhance the mechanical properties of the membrane and improve the adsorption properties of water-soluble dyes through surfactant groups.

Benefits of technology

The tensile strength and tensile strain of the composite film are significantly improved, the water flux and dye removal rate are enhanced, and the addition of modified aramid nanofibers improves the membrane's retention performance, with a removal rate of 98.53%, and the dyeing is improved. Efficiency of liquid wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066496240000081
    Figure BDA0005066496240000081
  • Figure BDA0005066496240000082
    Figure BDA0005066496240000082
  • Figure BDA0005066496240000083
    Figure BDA0005066496240000083
Patent Text Reader

Abstract

The invention belongs to the field of high polymer materials, and particularly provides a preparation method and application of a lignin-containing cellulose nanofiber / aramid nanofiber composite membrane. The preparation method comprises the following steps: extracting a lignin component in biomass powder by adopting a DMSO / KOH super alkali system, collecting the extracted DMSO for dissolving aramid fibers to realize surface modification of the aramid nanofibers by the lignin, and adding a protic solvent (water) to obtain the surface-modified aramid nanofibers. Carrying out DES treatment and ultrasonication on the precipitate treated by the super alkali system to obtain cellulose nanofibers containing lignin, mixing the cellulose nanofibers containing lignin with the modified aramid nanofibers, and then preparing the cellulose nanofiber / aramid nanofiber composite membrane containing lignin through a vacuum filtering device. The lignin-containing cellulose nanofiber / aramid nanofiber composite membrane prepared by the invention has excellent mechanical strength and dye liquor wastewater treatment capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a preparation method and application of a cellulose nanofiber / aramid nanofiber composite film containing lignin. Background Art

[0002] Since dye-rich wastewater with toxicity and carcinogenicity is discharged into natural water resources as industrial waste, it not only pollutes the environment but also threatens the survival of humans, animals and plants. Membrane separation technology has been rapidly developed in the purification of dye wastewater due to its simple operation, low energy consumption, environmental protection and high efficiency. Lignin-containing cellulose nanofibers (LCNFs) are a renewable and degradable nanofiber material with the characteristics of light weight, biocompatibility, high specific surface area, and high surface activity. It has great potential in the field of water treatment. However, the presence of rigid lignin causes the composite membrane to have disadvantages such as poor toughness and brittleness.

[0003] Aramid nanofibers (ANFs) are a new type of high-performance nanofibers with a highly tightly packed molecular structure. Due to their high crystallinity, strength and modulus, they are often introduced into polymers as reinforcing fillers to prepare high-performance composite materials. However, the surface of aramid nanofibers is chemically inert and has poor interfacial compatibility. Lignin, as a natural polar polymer with abundant reserves and rich aromatic structures, is expected to modify aramid nanofibers through chemical interactions and achieve surface activation of aramid nanofibers. At present, there are no reports in the published patents on the use of lignin to modify aramid nanofibers. Summary of the invention

[0004] The purpose of the present invention is to use a super strong base system to extract lignin to modify aramid nanofibers, and by virtue of the viscosity and homology of lignin, provide a method for preparing a cellulose nanofiber / aramid nanofiber composite membrane containing lignin and its application in dye wastewater treatment.

[0005] The present invention adopts the following technical solution:

[0006] A method for preparing a composite film of cellulose nanofibers / aramid nanofibers containing lignin, comprising the following steps:

[0007] (1) adding a certain amount of potassium hydroxide and biomass powder to dimethyl sulfoxide, reacting for a period of time, filtering, and collecting the supernatant and precipitate respectively;

[0008] (2) adding a certain amount of potassium hydroxide and aramid fibers to the supernatant in step (1), and stirring to form a uniform aramid nanofiber / dimethyl sulfoxide / potassium hydroxide solution;

[0009] (3) adding water to the solution in step (2) and stirring vigorously, and the formed uniform dispersion is filtered by vacuum and repeatedly washed with water to remove dimethyl sulfoxide and potassium hydroxide, and finally, the modified aramid nanofibers are dispersed in a certain amount of deionized water to form a modified aramid nanofiber dispersion (DANFs);

[0010] (4) the precipitate in step (1) is added to a deep eutectic solvent (DES) and reacted for a period of time, after which deionized water is added to terminate the reaction, and the mixture is washed with water until neutral by vacuum filtration, and the filter paper residue after washing is dispersed in a certain amount of deionized water to form a lignocellulose dispersion;

[0011] (5) The lignocellulose dispersion in step (4) is subjected to ultrasonic crushing to obtain a cellulose nanofiber dispersion containing lignin;

[0012] (6) The aramid nanofiber dispersion in step (3) and the lignin-containing cellulose nanofiber dispersion in step (5) are mixed in a certain proportion, and the mixed solution is ultrasonically treated to uniformly disperse the aramid nanofibers and the lignin-containing cellulose nanofibers, and then vacuum filtered and dried to form a lignin-containing cellulose nanofiber / aramid nanofiber composite membrane.

[0013] Furthermore, in step (1), the potassium hydroxide concentration is 3-5 mg / mL, the biomass powder is muskmelon vine powder, the reaction temperature is 30-120° C., and the reaction time is 1-24 h.

[0014] Furthermore, in step (2), the potassium hydroxide concentration is 3-5 mg / mL, the aramid nanofiber concentration is 1-5 mg / mL, the stirring temperature is 20-30° C., and the stirring speed is 300-800 r / min.

[0015] Furthermore, the vacuum filtration in step (3) is filtration at -0.1 MPa, the water washing is continuous addition of deionized water to ensure that the aramid nanofibers are in a wet state, and the concentration of the aramid nanofibers in the aramid nanofiber dispersion is 1-5 mg / mL.

[0016] Furthermore, the low eutectic solvent in step (4) is prepared by mixing choline chloride and oxalic acid dihydrate at 80° C. until a clear and transparent solution is formed, the reaction temperature of the precipitate and the low eutectic solvent is 90-120° C., the reaction time is 1-6 h, and the vacuum filtration is performed at -0.1 MPa.

[0017] Furthermore, the ultrasonic crushing time in step (5) is 1-3h.

[0018] Furthermore, in step (6), the proportion of aramid nanofibers in the lignin-containing cellulose nanofiber / aramid nanofiber composite membrane is 0-50%, and the drying is performed at a temperature of 30-80° C. for 12-24 hours.

[0019] The cellulose nanofiber / aramid nanofiber composite membrane containing lignin of the present invention adopts DMSO / KOH super alkali system to extract lignin components in biomass powder, collects the extracted DMSO to dissolve aramid fibers to achieve surface modification of aramid nanofibers by lignin, and obtains surface-modified aramid nanofibers by adding proton solvent (water). The precipitate treated by super alkali system is treated by DES and ultrasonically crushed to obtain cellulose nanofibers containing lignin, and mixed with modified aramid nanofibers, and then a cellulose nanofiber / aramid nanofiber composite membrane containing lignin is prepared by a vacuum filtration device. The aromatic structure of lignin is utilized to achieve surface modification of aramid nanofibers through π-π interaction and hydrogen bonding, and then a large number of hydrogen bonds are formed between the two fibers by means of the homology and viscosity of lignin, which greatly enhances the mechanical properties of the membrane; in addition, the surface active groups of lignin and cellulose give the composite membrane excellent water-soluble dye adsorption performance, thereby improving the interception performance of the membrane.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The super strong alkali system described in the present invention can not only realize the pretreatment of biomass powder, but also dissolve waste aramid fibers to prepare aramid nanofibers, and can be fully utilized.

[0022] (2) The method for modifying aramid nanofibers with lignin described in the present invention can reduce the surface inertness of aramid nanofibers, facilitate surface activation of aramid nanofibers, and improve interface compatibility.

[0023] (3) The cellulose nanofiber / aramid nanofiber composite membrane containing lignin described in the present invention realizes high-strength preparation of the composite membrane by utilizing the viscosity and polarity of the homologous lignin on the surfaces of cellulose nanofibers and aramid nanofibers. Compared with the unmodified aramid nanofibers, the tensile strength is increased by 84.9 MPa and the tensile strain is increased by 1.5%.

[0024] (4) The cellulose nanofiber / aramid nanofiber composite membrane containing lignin of the present invention was used for dye wastewater treatment. The addition of modified aramid nanofibers increased the water flux of the membrane from 11.31 L·m·s to 11.31 L·m·s without the addition of modified aramid nanofibers. -2 ·h -1 bar -1 Increased to 29.76L·m -2 ·h -1 bar-1 At the same time, the water-soluble dye solution can be efficiently removed, and the removal rate of methyl violet dye solution is increased from 68.38% without adding modified aramid nanofiber to 98.53%. The composite membrane of the present invention has potential application value in the field of dye wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a flow chart for preparing a cellulose nanofiber / aramid nanofiber composite membrane containing lignin according to the present invention;

[0026] Figure 2 This is a photo of the lignin-modified aramid nanofiber dispersion of the present invention;

[0027] Figure 3 This is a photo of the cellulose nanofiber dispersion containing lignin according to the present invention;

[0028] Figure 4 The photos of cellulose nanofiber / aramid nanofiber dispersion containing lignin with different addition amounts of modified aramid nanofibers;

[0029] Figure 5 The photos are of cellulose nanofiber / aramid nanofiber composite membranes containing lignin with different addition amounts of modified aramid nanofibers;

[0030] Figure 6 is the tensile stress-strain curve of the cellulose nanofiber / aramid nanofiber composite film containing lignin;

[0031] Figure 7 The flow rate change curve of cellulose nanofiber / aramid nanofiber composite membrane containing lignin to methyl violet dye solution;

[0032] Figure 8 Retention rate curve of cellulose nanofiber / aramid nanofiber composite membrane containing lignin for methyl violet dye solution. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with embodiments

[0034] Example 1

[0035] The method for preparing lignin-modified aramid nanocellulose described in this embodiment comprises the following steps:

[0036] (1) 0.3 g potassium hydroxide and 1 g citrus vine powder were added to 100 mL DMSO, the reaction temperature was 60°C, the reaction time was 12 h, and a DMSO extract (supernatant) and pretreated citrus vine powder (precipitate) were obtained;

[0037] (2) Add 0.5 g of potassium hydroxide to 100 mL of DMSO extract in step (1), add 0.2 g of aramid fiber, and stir at room temperature for one week to obtain a lignin-modified aramid nanofiber solution;

[0038] (3) mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, and heating and stirring in a water bath at 80° C. until the mixture becomes clear and transparent, thereby obtaining a deep eutectic solvent solution;

[0039] (4) adding the pretreated melon vine powder (1 g) in step (1) to the low eutectic solvent (100 g) in step (3), the reaction temperature is 110° C., the reaction time is 1 h, after the reaction is completed, the precipitate is washed with water by vacuum filtration until it is neutral, and dispersed in ultrapure water to obtain a cellulose dispersion containing lignin;

[0040] (5) adding an equal amount of ultrapure water to the lignin-modified aramid nanofiber solution in step (2), stirring vigorously for 30 minutes, washing with water to neutrality by vacuum filtration, and finally redispersing in ultrapure water to prepare a lignin-modified aramid nanofiber dispersion with a concentration of 1 mg / mL;

[0041] (6) placing the cellulose dispersion containing lignin in step (4) in an ultrasonic crushing device to prepare a cellulose nanofiber dispersion containing lignin with a concentration of 1 mg / mL;

[0042] (7) After the lignin-modified aramid fiber nanofiber dispersion in step (5) and the lignin-containing cellulose nanofiber dispersion in step (6) are mixed in a ratio of 1:9, 30 mL of the mixed dispersion is taken and filtered through a vacuum filtration device to obtain a lignin-containing cellulose nanofiber / aramid nanofiber composite membrane (LC / DA 10 ).

[0043] Example 2

[0044] The method for preparing lignin-modified aramid nanocellulose described in this embodiment comprises the following steps:

[0045] (1) 0.3 g potassium hydroxide and 1 g citrus vine powder were added to 100 mL DMSO, the reaction temperature was 60°C, the reaction time was 12 h, and a DMSO extract (supernatant) and pretreated citrus vine powder (precipitate) were obtained;

[0046] (2) Add 0.5 g of potassium hydroxide to 100 mL of DMSO extract in step (1), add 0.2 g of aramid fiber, and stir at room temperature for one week to obtain a lignin-modified aramid nanofiber solution;

[0047] (3) mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, and heating and stirring in a water bath at 80° C. until the mixture becomes clear and transparent, thereby obtaining a deep eutectic solvent solution;

[0048] (4) adding the pretreated melon vine powder (1 g) in step (1) to the low eutectic solvent (100 g) in step (3), the reaction temperature is 110° C., the reaction time is 1 h, after the reaction is completed, the precipitate is washed with water by vacuum filtration until it is neutral, and dispersed in ultrapure water to obtain a cellulose dispersion containing lignin;

[0049] (5) adding an equal amount of ultrapure water to the lignin-modified aramid nanofiber solution in step (2), stirring vigorously for 30 minutes, washing with water to neutrality by vacuum filtration, and finally redispersing in ultrapure water to prepare a lignin-modified aramid nanofiber dispersion with a concentration of 1 mg / mL;

[0050] (6) placing the cellulose dispersion containing lignin in step (4) in an ultrasonic crushing device to prepare a cellulose nanofiber dispersion containing lignin with a concentration of 1 mg / mL;

[0051] (7) After the lignin-modified aramid fiber nanofiber dispersion in step (5) and the lignin-containing cellulose nanofiber dispersion in step (6) are mixed in a ratio of 1:4, 30 mL of the mixed dispersion is taken and filtered through a vacuum filtration device to obtain a lignin-containing cellulose nanofiber / aramid nanofiber composite membrane (LC / DA 20 ).

[0052] Example 3

[0053] The method for preparing lignin-modified aramid nanocellulose described in this embodiment comprises the following steps:

[0054] (1) 0.3 g potassium hydroxide and 1 g citrus vine powder were added to 100 mL DMSO, the reaction temperature was 60°C, the reaction time was 12 h, and a DMSO extract (supernatant) and pretreated citrus vine powder (precipitate) were obtained;

[0055] (2) Add 0.5 g of potassium hydroxide to 100 mL of DMSO extract in step (1), add 0.2 g of aramid fiber, and stir at room temperature for one week to obtain a lignin-modified aramid nanofiber solution;

[0056] (3) mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, and heating and stirring in a water bath at 80° C. until the mixture becomes clear and transparent, thereby obtaining a deep eutectic solvent solution;

[0057] (4) adding the pretreated melon vine powder (1 g) in step (1) to the low eutectic solvent (100 g) in step (3), the reaction temperature is 110° C., the reaction time is 1 h, after the reaction is completed, the precipitate is washed with water by vacuum filtration until it is neutral, and dispersed in ultrapure water to obtain a cellulose dispersion containing lignin;

[0058] (5) adding an equal amount of ultrapure water to the lignin-modified aramid nanofiber solution in step (2), stirring vigorously for 30 minutes, washing with water to neutrality by vacuum filtration, and finally redispersing in ultrapure water to prepare a lignin-modified aramid nanofiber dispersion with a concentration of 1 mg / mL;

[0059] (6) placing the cellulose dispersion containing lignin in step (4) in an ultrasonic crushing device to prepare a cellulose nanofiber dispersion containing lignin with a concentration of 1 mg / mL;

[0060] (7) After the lignin-modified aramid fiber nanofiber dispersion in step (5) and the lignin-containing cellulose nanofiber dispersion in step (6) are mixed in a ratio of 3:7, 30 mL of the mixed dispersion is taken and filtered through a vacuum filtration device to obtain a lignin-containing cellulose nanofiber / aramid nanofiber composite membrane (LC / DA 30 ).

[0061] Example 4

[0062] The method for preparing lignin-modified aramid nanocellulose described in this embodiment comprises the following steps:

[0063] (1) 0.3 g potassium hydroxide and 1 g citrus vine powder were added to 100 mL DMSO, the reaction temperature was 60°C, the reaction time was 12 h, and a DMSO extract (supernatant) and pretreated citrus vine powder (precipitate) were obtained;

[0064] (2) Add 0.5 g of potassium hydroxide to 100 mL of DMSO extract in step (1), add 0.2 g of aramid fiber, and stir at room temperature for one week to obtain a lignin-modified aramid nanofiber solution;

[0065] (3) mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, and heating and stirring in a water bath at 80° C. until the mixture becomes clear and transparent, thereby obtaining a deep eutectic solvent solution;

[0066] (4) adding the pretreated melon vine powder (1 g) in step (1) to the low eutectic solvent (100 g) in step (3), the reaction temperature is 110° C., the reaction time is 1 h, after the reaction is completed, the precipitate is washed with water by vacuum filtration until it is neutral, and dispersed in ultrapure water to obtain a cellulose dispersion containing lignin;

[0067] (5) adding an equal amount of ultrapure water to the lignin-modified aramid nanofiber solution in step (2), stirring vigorously for 30 minutes, washing with water to neutrality by vacuum filtration, and finally redispersing in ultrapure water to prepare a lignin-modified aramid nanofiber dispersion with a concentration of 1 mg / mL;

[0068] (6) placing the cellulose dispersion containing lignin in step (4) in an ultrasonic crushing device to prepare a cellulose nanofiber dispersion containing lignin with a concentration of 1 mg / mL;

[0069] (7) After the lignin-modified aramid fiber nanofiber dispersion in step (5) and the lignin-containing cellulose nanofiber dispersion in step (6) are mixed in a ratio of 2:3, 30 mL of the mixed dispersion is taken and filtered through a vacuum filtration device to obtain a lignin-containing cellulose nanofiber / aramid nanofiber composite membrane (LC / DA 40 ).

[0070] Example 5

[0071] The method for preparing lignin-modified aramid nanocellulose described in this embodiment comprises the following steps:

[0072] (1) 0.3 g potassium hydroxide and 1 g citrus vine powder were added to 100 mL DMSO, the reaction temperature was 60°C, the reaction time was 12 h, and a DMSO extract (supernatant) and pretreated citrus vine powder (precipitate) were obtained;

[0073] (2) Add 0.5 g of potassium hydroxide to 100 mL of DMSO extract in step (1), add 0.2 g of aramid fiber, and stir at room temperature for one week to obtain a lignin-modified aramid nanofiber solution;

[0074] (3) mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, and heating and stirring in a water bath at 80° C. until the mixture becomes clear and transparent, thereby obtaining a deep eutectic solvent solution;

[0075] (4) adding the pretreated melon vine powder (1 g) in step (1) to the low eutectic solvent (100 g) in step (3), the reaction temperature is 110° C., the reaction time is 1 h, after the reaction is completed, the precipitate is washed with water by vacuum filtration until it is neutral, and dispersed in ultrapure water to obtain a cellulose dispersion containing lignin;

[0076] (5) adding an equal amount of ultrapure water to the lignin-modified aramid nanofiber solution in step (2), stirring vigorously for 30 minutes, washing with water to neutrality by vacuum filtration, and finally redispersing in ultrapure water to prepare a lignin-modified aramid nanofiber dispersion with a concentration of 1 mg / mL;

[0077] (6) placing the cellulose dispersion containing lignin in step (4) in an ultrasonic crushing device to prepare a cellulose nanofiber dispersion containing lignin with a concentration of 1 mg / mL;

[0078] (7) After the lignin-modified aramid fiber nanofiber dispersion in step (5) and the lignin-containing cellulose nanofiber dispersion in step (6) are mixed in a ratio of 1:1, 30 mL of the mixed dispersion is taken and filtered through a vacuum filtration device to obtain a lignin-containing cellulose nanofiber / aramid nanofiber composite membrane (LC / DA 50 ).

[0079] Comparative Example 1

[0080] The preparation method of lignin-modified aramid nanocellulose described in this comparative example consists of the following steps:

[0081] (1) 0.3 g potassium hydroxide and 1 g citrus vine powder were added to 100 mL DMSO, the reaction temperature was 60°C, the reaction time was 12 h, and a DMSO extract (supernatant) and pretreated citrus vine powder (precipitate) were obtained;

[0082] (2) mixing choline chloride and oxalic acid dihydrate in a molar ratio of 1:1, and heating and stirring in a water bath at 80° C. until the mixture becomes clear and transparent, thereby obtaining a deep eutectic solvent solution;

[0083] (3) adding the pretreated melon vine powder (1 g) in step (1) to the low eutectic solvent (100 g) in step (2), the reaction temperature is 110° C., the reaction time is 1 h, after the reaction is completed, the precipitate is washed with water by vacuum filtration until it is neutral, and dispersed in ultrapure water to obtain a cellulose dispersion containing lignin;

[0084] (4) placing the cellulose dispersion containing lignin in step (3) in an ultrasonic crushing device to prepare a cellulose nanofiber dispersion containing lignin with a concentration of 1 mg / mL;

[0085] (5) 30 mL of the lignin-modified aramid fiber nanofiber dispersion in step (4) was filtered through a vacuum filtration apparatus to obtain lignin-containing cellulose nanofiber membranes (LCNFs).

[0086] Application Example 1

[0087] A 100 mg / L methyl violet dye solution was prepared, and then the membranes prepared in Examples 1 to 5 and Comparative Example 1 were respectively fixed on the suction filtration separation device, and then 5 mL of methyl violet dye solution was added to the suction filtration device for a filtration experiment, and the filtrate was collected for ultraviolet spectrophotometer testing to obtain the interception result.

[0088] The three components of the melon vines before and after pretreatment in Examples 1 to 5 and Comparative Example 1 were analyzed, as shown in Table 1. DMSO / KOH can dissolve the extract and lignin in the melon vine powder and be used for the modification of aramid nanofibers. The mechanical properties of the membrane materials prepared in Examples 1 to 5 and Comparative Example 1 were analyzed, as shown in Tables 2 and Figure 6 As shown in Figure 2, with the increase of the content of lignin modified aramid nanofibers, Example 5 showed the best mechanical properties, with a tensile strength of up to 186.91 MPa and a toughness of up to 9.28 MJ / m 3 , Young's modulus is as high as 8.43 GPa. At the same time, the dye liquor interception performance of the membrane materials prepared in Examples 1 to 5 and Comparative Example 1 was analyzed, as shown in Tables 3 and Figure 7 , Figure 8 As shown in the figure, the flux and retention rate of the membrane both showed an increasing trend with the addition of lignin-modified aramid nanofibers, and the flux and retention rate of the composite membrane obtained in Example 5 reached the best quality, which were 29.76 L·m -2 ·h -1 bar -1 and 98.54%.

[0089] Table 1 The contents of three components in melon vines before and after DMSO / KOH pretreatment

[0090]

[0091] Table 2 Mechanical strength test results

[0092]

[0093] Table 3 Retention performance test results

[0094]

Claims

1. A method for preparing a cellulose nanofiber / aramid nanofiber composite membrane containing lignin and its application, characterized in that: It consists of the following steps: (1) adding a certain amount of potassium hydroxide and biomass powder to dimethyl sulfoxide, reacting for a period of time, filtering, and collecting the supernatant and precipitate respectively; (2) adding a certain amount of potassium hydroxide and aramid fibers to the supernatant in step (1), and stirring to form a uniform aramid nanofiber / dimethyl sulfoxide / potassium hydroxide solution; (3) adding water to the solution in step (2) and stirring vigorously, and the formed uniform dispersion is filtered by vacuum and repeatedly washed with water to remove dimethyl sulfoxide and potassium hydroxide, and finally, the modified aramid nanofibers are dispersed in a certain amount of deionized water to form a modified aramid nanofiber dispersion (DANFs); (4) the precipitate in step (1) is added to a low eutectic solvent and reacted for a period of time, after which deionized water is added to terminate the reaction, and the precipitate is washed with water until neutral by vacuum filtration, and the filter paper residue after washing is dispersed in a certain amount of deionized water to form a lignocellulose dispersion; (5) The lignocellulose dispersion in step (4) is subjected to ultrasonic crushing to obtain a cellulose nanofiber dispersion containing lignin; (6) The aramid nanofiber dispersion in step (3) and the lignin-containing cellulose nanofiber dispersion in step (5) are mixed in a certain proportion, and the mixed solution is ultrasonically treated to uniformly disperse the aramid nanofibers and the lignin-containing cellulose nanofibers, and then vacuum filtered and dried to form a lignin-containing cellulose nanofiber / aramid nanofiber composite membrane.

2. The preparation method and application of a cellulose nanofiber / aramid nanofiber composite membrane containing lignin according to claim 1, characterized in that: In step (1), the potassium hydroxide concentration is 3-5 mg / mL, the biomass powder is muskmelon vine powder, the reaction temperature is 30-120° C., and the reaction time is 1-24 h.

3. The preparation method and application of a cellulose nanofiber / aramid nanofiber composite membrane containing lignin according to claim 1, characterized in that: In step (2), the potassium hydroxide concentration is 3-5 mg / mL, the aramid nanofiber concentration is 1-5 mg / mL, the stirring temperature is 20-30° C., and the stirring speed is 300-800 r / min.

4. The preparation method and application of a cellulose nanofiber / aramid nanofiber composite membrane containing lignin according to claim 1, characterized in that: The vacuum filtration in step (3) is filtration at -0.1 MPa, the water washing is continuous addition of deionized water to ensure that the aramid nanofibers are in a wet state, and the concentration of the aramid nanofibers in the aramid nanofiber dispersion is 1-5 mg / mL.

5. The preparation method and application of a cellulose nanofiber / aramid nanofiber composite membrane containing lignin according to claim 1, characterized in that: The low eutectic solvent in step (4) is prepared by mixing choline chloride and oxalic acid dihydrate at 80° C. until a clear and transparent solution is formed. The reaction temperature of the precipitate and the low eutectic solvent is 90-120° C., the reaction time is 1-6 h, and the vacuum filtration is performed at -0.1 MPa.

6. The preparation method and application of a cellulose nanofiber / aramid nanofiber composite membrane containing lignin according to claim 1, characterized in that: The ultrasonic crushing time in step (5) is 1-3h.

7. The preparation method and application of a cellulose nanofiber / aramid nanofiber composite membrane containing lignin according to claim 1, characterized in that: In step (6), the proportion of aramid nanofibers in the lignin-containing cellulose nanofiber / aramid nanofiber composite membrane is 0-50%, and the drying is performed at a temperature of 30-80° C. for 12-24 hours.

Citation Information

Cited By

  • Preparation method of hollow nanofiber membrane

    CN120532327A